(untitled) (Scottish Historical and Archaeological Internet Reports, 2004)
The site was well placed for both fresh water and shelter as well as wider resources. Given the constraints of the data it would be unwise to attempt any detailed interpretation of the Mesolithic environment. With regard to the pollen data, comment will be limited to saying that all taxa are common indicators of open ground habitats. The only exception is the most frequently represented pollen grain on site, that of Corylus avellana-type (cf. hazel), of which 78 grains were found, as well as some macrofossil material. Hazel was an abundant member of Skye’s 8th millennium BP flora. The hazelnut shells from the excavation were thus probably collected locally.